Large‐Area Antenna‐Assisted SEIRA Substrates by Laser Interference Lithography. Issue 11 (31st July 2014) - Bagheri, Shahin; Giessen, Harald; Neubrech, Frank
<x xml:space="preserve">Abstract</x> Laser interference lithography is utilized to fabricate large‐area plasmonic antenna substrates for surface‐enhanced infrared absorption (SEIRA). Changing the interference condition in each exposure process allows precise control over the geometrical parameters of the structures and thus tailoring of their optical response. Independent of the underlying wafer, the technique enables a homogeneous preparation of antennas over cm2 areas with tunable and high‐quality plasmonic resonances in the near‐ and mid‐infrared spectral range. The broad applicability of such SEIRA substrates is demonstrated by enhancing the infrared vibrational signals of a monolayer octadecanethiol and by monitoring the ultraviolet degradation of a polymer via the decrease of its specific vibrational modes. Due to the large‐area and fast fabrication process, laser interference lithography is ideally suited for the preparation of low‐cost sensing platforms for a variety of different SEIRA applications in the chemical, analytical, and life sciences.